Mockingbird summer : a novel - Rutledge, Lynda, 1950- (Lake Union Publishing, 2024)
In segregated High Cotton, Texas, in 1964, the racial divide is as clear as the railroad tracks running through town. It's also where two girls are going to shake things up. This is the last summer of thirteen-year-old Corky Corcoran's childhood, and her family hires a Haitian housekeeper who brings her daughter, America, along with her. Corky is quick to befriend America and eager to share her favorite new "grown-up" novel, To Kill a Mockingbird. America's take on it is different and profoundly personal. As their friendship grows, Corky finds out so much more about America's life and her hidden skill: she can run as fast as Olympian Wilma Rudolph! When Corky asks America to play with her girls' softball team for the annual church rivals game, it's a move that crosses the color line and sets off a firestorm. As tensions escalate, it fast becomes a season of big changes in High Cotton. For Corky, those changes will last a lifetime.